Deductive verification of object-oriented software : dynamic frames, dynamic logic and predicate abstraction - Weiß, Benjamin (KIT Scientific Publishing, 2011)
Software systems play a central role in modern society, and their correctness is often crucially important. Formal specification and verification are promising approaches for ensuring correctness more rigorously than just by testing. This work presents an approach for deductively verifying design-by-contract specifications of object-oriented programs. The approach is based on dynamic logic, and addresses the challenges of modularity and automation using dynamic frames and predicate abstraction.